¿Real malicia? Descifrando un estándar foráneo de protección del derecho a la libertad de expresión para su aplicación en Ecuador - Ortiz Custodio, Jose David (2020)
Decision N° 282-13-JP/19, issued by the Constitutional Court of Ecuador. introduced the actual malice standard originated in the New York Times Co. vs. Sullivan case to analyze possible limitations to the right offreedom of speech. This standard applies in cases of publication of false and defamatory statement of facts on issues of public interest. The Constitutional Court ruled that persons involved in matters of public interest have at their disposal the mechanisms of reply and rectification to defend their reputation against the publication of information that they consider false, inaccurate or offensive; and, only if these mechanisms prove to be insufficient, they may file a civil complaint for defamation to claim compensation if they satisfy the actual malice standard. This article analyzes the origin of the actual malice standard in the New York Times Co. vs. Sullivan case to identify its nature and purposes as a stringent scrutiny to protect the right of freedom of speech and the principle that debate on public issues should be uninhibited, robust and wide-open. To do this, it examines the precedents of the United States Supreme Court to determine when the actual malice standard applies and how its configurative elements should be understood, and also outlines the main criticisms of the standard and the practical problems associated with its application. Finally, based on these findings, it examines how the standard of actual malice will be applied in Ecuador, in perspective of Decision N° 282-13-JP/19, issued by the Constitutional Court of Ecuador. In this way, the article makes a comparative analysis of the scope and the configurative elements of this foreign standard, according to the Ecuadorian legal framework.